2019
DOI: 10.1108/jstpm-02-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to and usage of e-banking channels

Abstract: Purpose Emphasis of previous research on e-banking has been on factors that influence its adoption or constraints to the adoption or the extent to which customer awareness influences its adoption. This study investigated “Exposure to/usage of e-banking channels: Implications for customer awareness and attitude in Nigeria”. The purpose of this paper is to determine the extent to which consumers’ exposure to and usage of e-banking channels influence their awareness and attitude towards e-banking in Nigeria. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The banks need to find a way to enhance customers' experience. This is because prior studies found out customers' experience influences their attitude to banking in Nigeria (Inegbedion et al 2019). One of the tweets observed in topic 1 highlighted bad staff attitude.…”
Section: Tsbs Visualizationmentioning
confidence: 96%
See 2 more Smart Citations
“…The banks need to find a way to enhance customers' experience. This is because prior studies found out customers' experience influences their attitude to banking in Nigeria (Inegbedion et al 2019). One of the tweets observed in topic 1 highlighted bad staff attitude.…”
Section: Tsbs Visualizationmentioning
confidence: 96%
“…Prior studies highlighted the importance of the transaction related topics, for example, customer service experience (Ugwuanyi et al 2020), internet service performance (Eke & Singhry, 2020;Oyelami et al 2020), bank charges (Haruna et al 2018, mobile banking (Inegbedion et al 2019), and credit card payment (Aduaka & Awolusi 2020) as key influencing factors of customers' attitude in the Nigeria banking industry. Very interesting but surprising, previous studies did not pay attention or investigate "transaction problem" and "contact/complaint form" explicitly.…”
Section: Summary Of the 10-lda Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In research conducted by Safari, attitude toward nonusers has a significant impact on behavior intention (Safari et al, 2020). Users' inability to exert perfect control over the product they choose to use at all times, as well as the absence of other system characteristics whose use can influence users' knowledge of and attitude toward information systems, are two of the most serious shortcomings of information systems (Inegbedion et al, 2019). This is consistent with research (Al-Gahtani, 2002), which shows that perceived usefulness and user attitudes have a significant influence on technology acceptance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The marketing function is one of the most important administrative functions in the organization and is specific to its success (Sampaio, Perin, Dolci, Santini, & Ladeira, 2019). The ability of any organization to produce goods and provide services is limited unless accompanied by an efficient marketing effort that helps to identify the customer's needs and increase the sales and profitability that the institution seeks to achieve (Osifo et al, 2019). The development of marketing activity in the banks over time, which led to a change in the philosophy and view of the management of the market, where this development has gone through many stages and the banking marketing occupies an important position in the administrative composition of the banking institution.…”
Section: Introductionmentioning
confidence: 99%